Effects of storage time and temperature on the characteristics of vegetable-type soybean grain minimally processed - Czaikoski,Karina (2012)
The objective of this study was to evaluate the effects of storage time and temperature on the characteristics of vegetable-type soybean grain (cultivar BRS 267) minimally processed and to define the best conditions for its storage. The evaluation was performed by measurement of vitamin C levels, weight loss and color parameters (L*, a*, and b*). The time of storage of vegetable-type soybean grains minimally processed and storage in Styrofoam trays and wrapped with PVC film, caused a decreased in vitamin C levels and color parameters and increased weight loss. This process was intensified with higher temperature at 25 °C than 5°C. To maintain appropriate levels of vitamin C, weight and color of vegetable-type soybean grains minimally processed and storage in trays wrapped in plastic wrap, recommended storage for 3 days at 5°C.